TOTAL FLAVONOID QUANTIFICATION AND TO STUDY ANTIBACTERIAL POTENCY OF EXTRACTS OF BUTEA MONOSPERMA FLOWERS, NIGELLA SATIVA SEEDS AND VITEX AGNUS CASTUS LEAVES - Jain, Kajal L.; Choudhury, P. K.; Sharma, Maya (International Journal of Current Pharmaceutical Research, 2017)
Objective: An attempt has been made to develop a method for quantitative estimation of flavonoids in the crude extract of Butea monosperma flowers, Nigella sativa seeds and Vitex agnus castus leaves. Antibacterial activity is attributed to various phytochemicals present in these plants. Methods: The amount of total flavonoids was analysed using aluminium chloride colorimetric assay using rutin as standard. Plants studied were subjected to hydromethanolic extraction by using soxhlet apparatus. Flavonoids in extracts were quantified by U. V at a wavelength of 415 nm Antibacterial activities of extracts were evaluated on various bacterias like E. coli, P. aeruginosa, S. aureus, S. pneumonie, P. acne. The in vitro antibacterial activities of these extracts were compared against standard drugs such as gentamycin, ampicillin, chloramphenicol, ciprofloxacin, norfloxacin. Results: Flavonoid content in the crude extract of Butea monosperma flowers, Nigella sativa seeds and Vitex agnus castus leaves was found to be 2.58 %w/w, 0.92% w/w and 1.6 % w/w respectively. The antibacterial study found that activity of Vitex extract against P. acne was better than the standard drugs Conclusion: In the present study an attempt has been made to standardize the plant material in terms of its flavonoid content and the study indicated that this extract individually or in combination with other herbal drugs can be useful in treating diseases caused by the organisms mentioned above.